Competitive removal of tetracycline and paracetamol in the sequencing batch reactor system - Celik, Aytekin (Elsevier Science Inc, 2022)
In this study, removal of both tetracycline (TC) and paracetamol (PCT) were investigated with syn-thetic wastewater with a sequencing batch reactor. TC and PCT were removed at maximum 62% and 99% under the same conditions which were hydraulic retention time, concentration of dissolved oxygen and acetate concentration, respectively. On the other hand, nitrification and denitrification efficiency were obtained as 95% and 99%. In terms of volumetric removal flux, TC and equivalent O-2 flux of TC were calculated as maximum 2.3 and 4.40 mg/L.d. Likewise, the maximum removal volumetric flux of PCT and its O-2 equivalent flux were determined as 135.9 and 303.1 mg/L.d. The results showed that aerobic bacteria preferred PCT rather than TC.
Keywords: Equivalent flux; Paracetamol; Pharmaceuticals; Sequencing batch reactor; Tetracycline; Volumetric flux